Characterization of a Severe Parenchymal Phenotype of Experimental Autoimmune Encephalomyelitis in (C57BL6xB10.PL)F1 Mice - Carrithers, Michael D. (2007)
We here describe a novel CD4 T cell adoptive transfer model of severe experimental autoimmune encephalomyelitis in (C57BL6xB10.PL)F1 mice. This FI cross developed severe disease characterized by extensive parenchymal spinal cord and brain periventricular white matter infiltrates. In contrast, B10.PL mice developed mild disease characterized by meningeal predominant infiltrates. As determined by cDNA microarray and quantitative real time PCR expression analysis, histologic and flow cytometry analysis of inflammatory infiltrates, and attenuation of disease in class I-deficient and CD8-depleted F1 mice; this severe disease phenotype appears to be regulated by CNS infiltration of CD8 T lymphocytes early in the disease course.